1995
DOI: 10.1002/j.1460-2075.1995.tb07008.x
|View full text |Cite
|
Sign up to set email alerts
|

An acute myeloid leukemia gene, AML1, regulates hemopoietic myeloid cell differentiation and transcriptional activation antagonistically by two alternative spliced forms.

Abstract: The AML1 gene on chromosome 21 is disrupted in the (8;21)(q22;q22) and (3;21)(q26;q22) translocations associated with myelogenous leukemias and encodes a DNA binding protein. From the AML1 gene, two representative forms of proteins, AML1a and AML1b, are produced by alternative splicing. Both forms have a DNA binding domain but, unlike AML1b, AML1a lacks a putative transcriptional activation domain. Here we demonstrate that overexpressed AML1a totally suppresses granulocytic differentiation and stimulates cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
217
1
4

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(238 citation statements)
references
References 50 publications
16
217
1
4
Order By: Relevance
“…One example is the generation of blast crisis in Philadelphia chromosome-positive chronic myelogenous leukemia (Ph1 + CML), where after entering blast crisis, the chimeric BCR/ABL transcript is noted to use the BCR exon b3 preferentially over exon b2 in a number of cases. 43,44 A second example seen in both AML and acute lymphoid leukemias (ALL), is the expression of an alternatively spliced form of the Src-related protein tyrosine kinase, Lck. 43 Normally, type IIA is highly expressed in T lymphocytes, with B lymphocytes expressing type IB, but at very low levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One example is the generation of blast crisis in Philadelphia chromosome-positive chronic myelogenous leukemia (Ph1 + CML), where after entering blast crisis, the chimeric BCR/ABL transcript is noted to use the BCR exon b3 preferentially over exon b2 in a number of cases. 43,44 A second example seen in both AML and acute lymphoid leukemias (ALL), is the expression of an alternatively spliced form of the Src-related protein tyrosine kinase, Lck. 43 Normally, type IIA is highly expressed in T lymphocytes, with B lymphocytes expressing type IB, but at very low levels.…”
Section: Discussionmentioning
confidence: 99%
“…A study of AML patient samples has also identified increased expression of a splice variant of the transcription factor AML1 that is associated with the leukemic phenotype. 44 This splice variant (AML1a) is also produced by recognition of cryptic splice donor and acceptor sites in the carboxy-terminal region of the transcript, similar to how the class IV G-CSFR isoform is derived. This results in a DNA binding protein without the transcriptionally active domain and presumably acts via a dominant-negative mechanism to inhibit transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is the fusion protein generated in about one fourth of pediatric B-cell ALL patients, as a result of the t(12;21) translocation (Romana et al, 1995;Shurtleff et al, 1995). Normally, AML1 positively regulates a number of genes required for hematopoiesis (Okuda et al, 1996;Wang et al, 1996;Tanaka et al, 1997), whereas repression of these genes by TEL-AML1 and its interacting corepressors is thought to contribute to the leukemic phenotype (Frank et al, 1995;Fears et al, 1997;Uchida et al, 1997;Guidez et al, 2000). Similarly, a common translocation in AML patients, t(8;21) results in the generation of fusion protein AML1 and ETO (eight-twenty-one or MTG8), which also recruits corepressors and HDACs by the C terminus of ETO, leading to repression of the AML1 target genes (Rowley, 1982;Erickson et al, 1992;Gelmetti et al, 1998;Lutterbach et al, 1998;Wang et al, 1998;Amann et al, 2001).…”
Section: Hdac3 In Leukemiamentioning
confidence: 99%
“…[9][10][11] Several model systems have documented the ability of AML1-ETO to inhibit the differentiation of myeloid cell lines in response to chemical signals. [12][13][14] However, the use of cell lines may not accurately model the functional effects of AML1-ETO expression, owing to the different complement of transcription factors found in transformed cells versus hematopoietic progenitor cells (HPCs).…”
Section: Introductionmentioning
confidence: 99%